2021
DOI: 10.3390/vaccines9040380
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Have COVID-19 Vaccination Explained Using an Extended Protection Motivation Theory among University Students in China: The Role of Information Sources

Abstract: Background: The aims of the present study were to examine the prediction of the threat and coping appraisal utilizing an extended protection motivation theory (PMT) for the motivation to have COVID-19 vaccination and the influence of various information sources on coping appraisal among university students in China. Methods: The sample comprised 3145 students from 43 universities in China who completed an online survey including PMT constructs as well as constructs added to PMT. The PMT constructs comprised mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 41 publications
11
128
5
1
Order By: Relevance
“…A previous study revealed that the availability of vaccination information might affect students’ coping strategies. 44 Therefore, further studies and interventions are needed, especially in the presence of an effective vaccine. Second, our study was conducted at one university in a single city which may limit the generalization of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the availability of vaccination information might affect students’ coping strategies. 44 Therefore, further studies and interventions are needed, especially in the presence of an effective vaccine. Second, our study was conducted at one university in a single city which may limit the generalization of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, perceived vulnerability, perceived severity, and response cost of COVID-19 vaccination were positively associated with motivation to receive COVID-19 vaccination among the public but not among frontline HCWs. A study also found that perceived severity of COVID-19 was positively associated with motivation to receive COVID-19 vaccination among university students in China [36], indicating that increasing individuals' threat appraisal of COVID-19 may be an effective method of increasing motivation to receive a COVID-19 vaccination for non-HCWs. Programs promoting COVID-19 vaccination for the public can use narrative communication as a tool (e.g., inviting the patients to convey the severity of contracting COVID-19) [40].…”
Section: Pmt Factors Related To Motivation To Receive Covid-19 Vaccination In Frontline Hcws and In The Publicmentioning
confidence: 95%
“…Although the factors examined in these studies are included in the threat and coping appraisals of PMT, no study has examined the comprehensive PMT constructs that relate to frontline HCW motivation to receive COVID-19 vaccination. A study applying PMT found that threat appraisal but not coping appraisal predicted motivation to receive COVID-19 vaccination among university students in China [36]. Given that frontline HCWs face a direct threat from COVID-19, it is reasonable to hypothesize that frontline HCWs have a higher level of motivation to receive COVID-19 vaccination than members of the public do.…”
Section: Protection Motivation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a small number of COVID-19 PMT studies, including 734 healthcare workers in Iran [ 25 ], 649 Filipinos answering an online questionnaire [ 26 ], and 3145 students from 43 universities in China [ 27 ]. The online survey of Chinese students found that the perceived severity of COVID-19 was positively associated with motivation to have COVID-19 vaccination and receiving COVID-19 information from medical personnel was associated with greater self-efficacy, response efficacy, and knowledge, whereas receiving information concerning COVID-19 vaccination from coworkers/colleagues was associated with less response efficacy and knowledge.…”
Section: Introductionmentioning
confidence: 99%